The Effect of Stem-Based Mathematics Learning on Students’ Critical and Creative Thinking Skills at SMA It Yarsi Mataram - Haerorroni, Haerorroni; Astuti, Alfira Mulya; Hardiani, Nur (Perspektif Ilmu Pendidikan, 2025)
Abstract: This study aims to: (1) explain the significant effect of STEM-based mathematics learning on students’ critical thinking skills; (2) explain the significant effect of STEM-based mathematics learning on students’ creative thinking skills; and (3) explain the significant effect of STEM-based mathematics learning on students’ critical and creative thinking skills at SMA IT Yarsi Mataram. The research employed a quantitative approach with a survey research design, which was selected to obtain systematic and structured data regarding students’ characteristics. The study was conducted at SMA IT Yarsi Mataram, with the population consisting of all eleventh-grade students, while the research sample comprised 53 students. The data collection instrument was a questionnaire distributed manually. The collected data were analyzed using multivariate regression analysis. The results indicate that: (1) STEM-based mathematics learning does not have a significant effect on students’ critical thinking skills, as shown by a univariate test significance value of 0.971, which is greater than the 0.05 significance level; (2) the STEM approach does not have a significant effect on students’ creative thinking skills, with a univariate test significance value of 0.147, exceeding 0.05; and (3) STEM-based mathematics learning does not show a significant effect on students’ critical and creative thinking skills simultaneously, as indicated by a Wilks’ Lambda significance value of 0.276, greater than 0.05. The implications of this study suggest that STEM-based mathematics learning cannot yet be considered an effective alternative learning strategy for developing higher-order thinking skills, particularly critical and creative thinking, highlighting the need for further research to explore learning models better suited to the characteristics of high school students. Keywords: STEM-Based Mathematics Learning, Critical Thinking, Creative Thinking